Sleep-related declarative memory consolidation and verbal replay during sleep talking in patients with REM sleep behavior disorder. - Ginevra Uguccioni; Olivier Pallanca; Jean-Louis Golmard; Pauline Dodet; Bastien Herlin; Smaranda Leu-Semenescu; Isabelle Arnulf (PLoS ONE, 2013)
OBJECTIVE: To determine if sleep talkers with REM sleep behavior disorder (RBD) would utter during REM sleep sentences learned before sleep, and to evaluate their verbal memory consolidation during sleep. METHODS: Eighteen patients with RBD and 10 controls performed two verbal memory tasks (16 words from the Free and Cued Selective Reminding Test and a 220-263 word long modified Story Recall Test) in the evening, followed by nocturnal video-polysomnography and morning recall (night-time consolidation). In 9 patients with RBD, daytime consolidation (morning learning/recall, evening recall) was also evaluated with the modified Story Recall Test in a cross-over order. Two RBD patients with dementia were studied separately. Sleep talking was recorded using video-polysomnography, and the utterances were compared to the studied texts by two external judges. RESULTS: Sleep-related verbal memory consolidation was maintained in patients with RBD (+24±36% words) as in controls (+9±18%, p=0.3). The two demented patients with RBD also exhibited excellent nighttime consolidation. The post-sleep performance was unrelated to the sleep measures (including continuity, stages, fragmentation and apnea-hypopnea index). Daytime consolidation (-9±19%) was worse than night-time consolidation (+29±45%, p=0.03) in the subgroup of 9 patients with RBD. Eleven patients with RBD spoke during REM sleep and pronounced a median of 20 words, which represented 0.0003% of sleep with spoken language. A single patient uttered a sentence that was judged to be semantically (but not literally) related to the text learned before sleep. CONCLUSION: Verbal declarative memory normally consolidates during sleep in patients with RBD. The incorporation of learned material within REM sleep-associated sleep talking in one patient (unbeknownst to himself) at the semantic level suggests a replay at a highly cognitive creative level.